Drivers of vegetable market participation in southcentral Ethiopia: Heckman two-stage model approach - Amanuel Ayele Gebre; Mahadeo S. Deshmukh (Discover Food)
Abstract Vegetable marketing helps to increase household income and ensure food and nutrition security in developing countries, including Ethiopia. However, market participation by vegetable producers is typically low in many parts of Ethiopia. Thus, our study intends to investigate key drivers affecting vegetable market participation and its intensity among smallholder households in the Lemo district of southcentral Ethiopia. The data were collected from a total of 345 randomly selected respondents. Heckman’s two-stage model was employed to analyze the data. The findings show that the intensity of vegetable sales in the study area was 34.32%, implying that the larger proportion of the vegetable output was not marketed but consumed at the producers’ homes.The model results show that the respondent’s sex, age, education level, land size, perception towards weather conditions, access to credit, technology adoption, and market distance influenced vegetable market participation. Similarly, education level, family size, off/non-farm income, perception towards weather conditions, access to credit, technology adoption, and market information determined the intensity of vegetable market participation. Therefore, policies aimed at enhancing the implementation of gender-sensitive development programs alongside providing better access to adult education, credit, market information, improved technologies, better rural infrastructure, and market linkages are recommended to encourage smallholder farmers’ involvement in the market and enhance their livelihood improvement.